Synchronized sexual reproduction of the seagrass Syringodium filiforme (Cymodoceaceae) in a tropical reef lagoon on the Caribbean coast of Costa Rica - Samper-Villarreal, Jimena; Loría-Naranjo, Margarita; van Tussenbroek, Brigitta Ine; Cortés, Jorge (Revista Ciencias Marinas y Costeras, 2020)
There has been an increasing effort to understand the mechanisms of sexual reproduction in seagrasses, which is usually synchronized. Synchronization is caused by environmental cues, such as temperature and light availability, and most likely occurs to maximize pollination success. At higher latitudes where seagrass reproductive seasons are clearly marked, intraannual variability of environmental triggers is significant. Our aim was to identify the period and frequency of sexual reproduction for the manatee grass Syringodium filiforme in a tropical coral reef lagoon, where the above-mentioned environmental triggers are homogenous all year round. The reproductive state and frequency and shoot length of S. filiforme were measured non-destructively in a monospecific patch on the tropical Caribbean coast of Costa Rica. The meadow was surveyed at 1 to 4-month intervals between May 2010 and May 2012. Water turbidity, temperature, and salinity were measured in situ. During the surveyed period, sexual reproduction of S. filiforme was detected in February and May, while seagrass shoot length showed no variation. The moment of seagrass sexual reproduction was not fully explained by the environmental parameters studied. Regardless of the limited environmental variability compared to previous studies at higher latitudes, synchronization of seagrass sexual reproduction at this tropical location is interesting and requires further studies on mechanisms and its possible adaptive advantage.